The relationship between cortical auditory evoked potentials (CAEPs) and speech perception in children with Nurotron® cochlear implants during four years of follow-up. (June 2016) - Guo, Qianqian; Li, Yuling; Fu, Xinxing; Liu, Hui; Chen, Jing; Meng, Chao; Long, Mo; Chen, Xueqing
Abstract: Objective: The purpose of the current study was to evaluate the relationship between the presence or absence of cortical auditory evoked potentials (CAEPs) to speech stimuli and the performance of speech perception in Chinese pediatric recipients of the Nurotron ® cochlear implant (CI).We also wanted to determine how the CAEPs might be used as an indicator for predicting early speech perception and could provide objective evidence for clinical applications of CAEPs. Methods: 23 pediatric unilateral CI recipients participated in this study. 15 males 8 females, and their ages at implantation ranged from 13 to 68 months, with a mean age of 36 months. CAEPs and Mandarin Early Speech Perception (MESP) tests were used to evaluate the audibility and speech perception of these CI users. The tests were administered at the first, second, third, and fourth year after the CI surgery. Results: All the subjects demonstrated improvements in detection of speech sounds with CI. The percentages of participants who could detect all three stimuli were 26% (6/23) at first year, to 100% (23/23) at the fourth year post-implantation. The percentages of participants who passed the Category 6 of MESP were from 9% (2/23) at first year, to 91% (21/23) at the fourth year post-implantation. Significant correlations ( p  < 0.05) were found between CAEP scores and MESP at the first, second, third year after the CI surgery. The multiple regression equation for prediction of MESP categories from CAEP scores and hearing ages was MESP = 1.088 + (0.504 × CAEP score) + (0.964 × hearing ages) ( F  = 72.919, p  < 0.001, R 2  = 0.621). Conclusion: The results of this study suggested that aided cortical assessment was a useful tool to evaluate the outcomes of cochlear implantation. Cortical outcomes had a significant positive relationship with the MESP, which predicted the early speech perception of CI recipients.